Effects of Technology, Energy, Monetary, and Fiscal Policies on the Relationship between Renewable and Fossil Fuel Energies and Environmental Pollution: Novel NBARDL and Causality Analyses - Bildirici, Melike; Cirpici, Yasemin Asu; Ersin, Ozgur Omer (MDPI, 2023)
There is a body of research that focuses on the examination of long-run relations between energy-environment-economic growth, and there is also a new type of recent research that focuses on the effects of monetary and fiscal economic policies on the environment. There is a research gap that exists due to omitting the effects of technology and energy policies, and this paper addresses this gap, in addition to merging both fields mentioned above, by including the asymmetric effects of fiscal and monetary policies. To explore the relations between fossil fuel and renewable energies, environmental pollution, and economic growth, in addition to including the roles of energy, technology, monetary, and fiscal policies, this paper employs novel NBARDL and NBARDL Granger Causality methods for yearly data assessments in the USA. The empirical findings of the paper point to the asymmetric impacts of monetary and fiscal policies in the short- and long-run. Interestingly, both contractionary and expansionary fiscal policies lead to higher CO2 emissions. Contractionary monetary policies exert a downward pressure on CO2 emissions, and if expansionary, the monetary policy causes environmental degradation. As an important policy, the energy policy emerges as a potent tool for reducing carbon emissions through not only renewable energy, but as a greater impact through energy efficiency and technology. Therefore, this paper highlights the importance of technology policies exhibiting varying relationships with environmental pollution, featuring unidirectional or bidirectional causality patterns. Renewable energy, energy efficiency combined with adequate technology, and energy policies are determined to have pivotal roles in CO2 emissions outcomes. Such policies should focus on cleaner energy sources accompanied by energy efficiency technologies in the USA to curtail environmental impacts; technology policies are vital in fostering innovations and encouraging cleaner technologies. The policy recommendations include an effective combination of monetary, fiscal, technology, and energy policies, backed by a strong commitment to achieving energy efficiency and renewable energy to mitigate environmental pollution and to contribute to sustainable development.
Keywords: environmental pollution; energy; renewable energy; monetary policy; fiscal policy; energy policy; technology policy; economic growth; causality; nonlinearity; BARDL; CO2 EMISSIONS; CARBON TAXES; GOVERNMENT EXPENDITURE; ECONOMIC-GROWTH; IMPACT; TAXATION; QUALITY; CHINA; Science & Technology - Other Topics; Environmental Sciences & Ecology